2014
DOI: 10.1089/end.2013.0051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes After Minimally Invasive Versus Open Partial Nephrectomy with Respect to Trainee Involvement Utilizing the American College of Surgeons National Surgical Quality Improvement Program

Abstract: This is the first report utilizing ACS NSQIP to review surgical approaches as well as the impact of trainee involvement on clinical outcomes. The increased complication rates and cost of healthcare might be mitigated by awareness, investment in surgical simulation laboratories, and competency assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…A large study utilizing the National Surgical Quality Improvement Program (NSQIP) Database found that resident and fellow involvement in renal surgery was associated with higher superficial and overall surgical site infection (SSI) (p<0.05). In addition, PGY 6 resident and fellow involvement was associated with higher organ space infections and overall SSI (p<0.05) [17]. Several other studies in our field, however, have failed to demonstrate an increased risk of complications relative to learner participation [1118].…”
Section: Discussionmentioning
confidence: 99%
“…A large study utilizing the National Surgical Quality Improvement Program (NSQIP) Database found that resident and fellow involvement in renal surgery was associated with higher superficial and overall surgical site infection (SSI) (p<0.05). In addition, PGY 6 resident and fellow involvement was associated with higher organ space infections and overall SSI (p<0.05) [17]. Several other studies in our field, however, have failed to demonstrate an increased risk of complications relative to learner participation [1118].…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15] In an increasingly cost-conscious medical culture, delivering high quality care is of utmost importance, translating in greater involvement of attending surgeons and less resident independence. 12 Moreover, surgical resident education is increasingly challenging due to expense, 19 work hour limitations 20 and an ever-increasing array of minimally-invasive surgical options to complement open surgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…This has been evaluated in the past in the general surgery literature with mixed results, while data on safety of resident participation in minimallyinvasive urologic surgery is limited. [10][11][12][13][14][15] We examine the impact of resident involvement on critical perioperative outcomes, including operative time, complications, readmission and reoperation rates, as well as length-of-stay. We assessed these endpoints for the commonly performed minimally-invasive urologic oncology procedures using data from American College of Surgeons National Surgery Quality Improvement Program (ACS-NSQIP) participating hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple evaluations of the NSQIP by general surgeons have found an increase in 30‐day complication rates associated with resident involvement in a broad array of general surgery procedures . Increased morbidity associated with resident operative involvement has been seen in orthopedics, plastic surgery, and urology . It has been proposed that increased postoperative morbidity may result from the prolonged operative time associated with resident involvement by way of surgical site infections and venous thromboembolic events from stasis, not necessarily from operative error .…”
Section: Discussionmentioning
confidence: 99%